Effects of antibiotic on microflora in ileum and cecum for broilers by 16S rRNA sequence analysis. (25th October 2018) - She, Yue; Cai, Huiyi; Liu, Guohua
Abstract: An experiment was conducted to analyze and compare the microbial composition, abundance, dynamic distribution, and functions without and with antibiotic fed to broilers. A 16S rRNA‐sequencing approach was used to evaluate the bacterial composition of the gut of male broilers under different groups. A total of 240 1‐day old AA male broilers were randomly assigned to two groups, with 120 broilers per group. The treatment group was administered an antibiotic with their feed, while the control group was not administered antibiotic (control group). A total of 10 replicates were assessed per treatment. The control group was fed a basal diet containing corn, soybean meal, and cottonseed meal and met the nutritional requirement. The antibiotic group was fed 100 mg/kg aureomycin (based on the basal diet). The trial lasted 42 days. Operational taxonomic unit partition and classification, alpha diversity, taxonomic composition, beta diversity, and microflora comparative analyses along with key species screening were performed for all of the treatment groups. Our data indicate that aureomycin treatment in broilers is directly correlated with variations of the gut content of specific bacterial taxa, and herein provide insights into the impact of antibiotic on microbial communities in cecum and ileum of broiler chickens.